Computer architecture digital circuits to microprocessors - Arroz, Guilherme; Monteiro, Jose; Oliveira, Arlindo L. (World Scientific Pub., 2019)
An introductory text to computer architecture, this comprehensive volume covers the concepts from logic gates to advanced computer architecture. It comes with a full spectrum of exercises and web-downloadable support materials, including assembler and simulator, which can be used in the context of different courses. The authors also make available a hardware description, which can be used in labs and assignments, for hands-on experimentation with an actual, simple processor.